PERAN IDEOLOGI DALAM MEMBENTUK ORIENTASI POLITIK MASYARAKAT - Fikri Mubarok, Encep; Hermansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Ideology is a fundamental concept in political science that plays an important role in shaping society’s political orientation. Political orientation encompasses cognitive, affective, and evaluative dimensions that influence how people understand, perceive, and assess political systems and practices. Amid social dynamics, globalization, and rapid developments in information technology, ideology becomes increasingly significant in maintaining the consistency and rationality of political attitudes. This study aims to describe the concept of ideology in contemporary political science, analyze society’s political orientation from a modern perspective, and explain the role of ideology in shaping political orientation. This research employs a qualitative approach using a literature review method by examining relevant academic publications. Data were analyzed using a descriptive-analytical technique through reviewing and synthesizing findings from various sources. The results indicate that ideology plays a central role in shaping political orientation and functions as a value framework that helps society interpret political realities and evaluate public policies. Therefore, strengthening ideological understanding through political education and socialization is essential.